Integrasi Nilai Multikultural Tradisi Kupatan melalui Pendekatan Futurologi dalam Pembelajaran Bahasa Indonesia Berbasis Kearifan Lokal di SMP - Muyassaroh; Bela Nofitasari; Zona Wijayanti (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study explores the integration of multicultural values embedded in the Kupatan tradition of Durenan District as a futurological and local wisdom-based approach to junior high school Indonesian language learning. The Kupatan tradition, a local cultural heritage, is not only a religious symbol but also embodies values of togetherness, tolerance, and mutual respect that are essential to maintaining social cohesion in a multicultural society. The futurological approach aims to design learning that equips students with future-oriented awareness rooted in inclusive cultural values. This research employs a descriptive qualitative method with data collected through observation, interviews, and literature review. The findings indicate that the Kupatan tradition holds multicultural values that can be integrated into Indonesian language teaching, especially in narrative and expository texts. Such integration enriches learning content and fosters students' openness to cultural diversity while preparing them for future global challenges. Thus, the Kupatan tradition holds strong potential as an alternative teaching material that is contextual, educational, and visionary in Indonesian language education at the junior high school level.